Beurteilung und Selbstbeurteilung im Studienbegleitenden Deutschunterricht - AMELINA, Svitlana (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
The article deals with questions of evaluation and self-evaluation of knowledge of foreign language of students in the learning process in higher education. Approaches to the evaluation of the „Framework Program in German language for professional communication for higher educational institutions of Ukraine” are presented.